2007
DOI: 10.5465/amj.2007.24634438
|View full text |Cite
|
Sign up to set email alerts
|

A New Model of Work Role Performance: Positive Behavior in Uncertain and Interdependent Contexts

Abstract: We propose that interdependence in a work context determines to what extent work roles are embedded within a broader social system and, further, that uncertainty determines whether work roles can be formalized or whether they emerge through adaptive and proactive behavior. Cross-classification of task, team member, and organization member behaviors with proficiency, adaptivity, and proactivity produced nine subdimensions of work role performance. Ratings from 491 supervisors from 32 organizations and self-rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
2,293
9
60

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,929 publications
(2,509 citation statements)
references
References 48 publications
38
2,293
9
60
Order By: Relevance
“…Ghiţulescu (2006) showed that the combination of discretion and task interdependence significantly predicted one or more forms of job crafting. Griffin et al (2007) highlighted the importance of the role played by context, especially the degree of unpredictability and task interdependence, in determining the amount and type of job crafting. Berg et al (2010a) have suggested that the role of perceived job crafting opportunities may be more complex than first thought.…”
Section: The Meaning Of Job Craftingmentioning
confidence: 99%
“…Ghiţulescu (2006) showed that the combination of discretion and task interdependence significantly predicted one or more forms of job crafting. Griffin et al (2007) highlighted the importance of the role played by context, especially the degree of unpredictability and task interdependence, in determining the amount and type of job crafting. Berg et al (2010a) have suggested that the role of perceived job crafting opportunities may be more complex than first thought.…”
Section: The Meaning Of Job Craftingmentioning
confidence: 99%
“…Thus, Griffin, Neal and Parker (2007) identified individual proactivity, team member proactivity, and organization member proactivity. These are effectively all types of proactive work behavior (Parker and Collins' higher order category) in that they aim to take control of, and bring about change within, the internal organization environment.…”
Section: Similarities and Differences In Proactive Behaviormentioning
confidence: 99%
“…These issues have led researchers to suggest that a more useful way of understanding proactivity is in terms of a dimension that is distinct from in-role and extra-role behavior (and the related dimension of task/ contextual performance). Thus, all types of performance -whether they are defined as task, conceptual, citizenship, or extra-role -can be carried out more or less proactively (Crant, 2000;Grant & Ashford, 2008;Griffin et al, 2007).…”
Section: Issues Around the Conceptualization Of Proactivitymentioning
confidence: 99%
“…In fact, researches have shifted from a focus on fixed tasks associated with the jobs to encompass a broader perspective in a dynamic organizational context (Ilgen and Hollenbeck 1991). Traditionally, performance was evaluated in terms of the proficiency with which an individual carried out the tasks that were prescribed in his or her role descriptions (Griffin et al 2007). This conceptualization is in tandem with those of earlier scholars (such as Katz 1964;Katz and Kahn 1978).…”
Section: Job Performancementioning
confidence: 99%